Evaluating the biocompatibility and biological performance of FePt-decorated nano-epoxy nanoparticles in mesenchymal stem cells. Issue 12 (2nd December 2021) - Chou, Ruey-Hwang; Yang, Meng-Yin; Yang, Yi-Ping; Yeh, Chun-An; Lai, Wei-Yi; Lin, Tzu-Wei; Teng, Yuan-Chi; Hsieh, Shu-Chen; Kung, Mei-Lang; Hsieh, Hsien-Hsu; Hung, Huey-Shan
Abstract : Background: Nanoparticles have wide potential applications in biolabeling, bioimaging, and cell tracking. Development of dual functional nanoparticles increases the versatility. Methods: We combined the fluorescent property of nano-epoxy (N-Epo) and the magnetic characteristic of FePt to fabricate the FePt-decorated N-Epo (N-Epo-FePt). The size in diameter of N-Epo-FePt (177.38 ± 39.25 nm) was bigger than N-Epo (2.28 ± 1.01 nm), both could be absorbed into mesenchymal stem cells (MSCs) via clathrin-mediated endocytosis and have multiple fluorescent properties (blue, green, and red). Results: N-Epo-FePt prevented N-Epo-induced platelet activation, CD68 + -macrophage differentiation in blood, and intracellular ROS generation in MSCs. The induction of apoptosis and the inhibitory effects of N-Epo-FePt on cell migration, MMP-9 activity, and secretion of SDF-1α were less than that of N-Epo in MSCs. Conclusion: N-Epo-FePt was more biocompatible without altering biological performance than N-Epo in MSCs. These results suggest that N-Epo-FePt nanoparticle can be used for fluorescence labeling of MSCs and is potential to apply to bioimaging and cell tracking of MSCs in vivo by magnetic resonance imaging or computed tomography.